Identifying lint properties of some cotton genotypes (Gossipum hirsutum L.) using different statistical models - Lina Q. Ahmed; Bahar J. Mahmood; Kazhal K,Muhammad (Zanco Journal of Pure and Applied Sciences, 2023)
The study was conducted to compare between nine cottonseeds genotypes (Gossipum hirsutum L) which included, two locale Iraqi genotypes Coker 310 and Lachata are and three of the Bakhtegan, Khordad, Varamin genotypes are from Iran, and four of them Cafko, Dunn 1047, Montana, Stoneville genotypes are from America (USA) on the fiber quality. The field experiment was designed with randomised complete block design using three replicates in Grdmal village, south Erbil, which is 30 km far from centre of Erbil, Iraq. Statistical analysis of the traits shown significant differences among the nine cotton genotypes, significantly maximum fiber strength, fiber elongation protein yield (33.20, 6.80 and 118.27) was recorded by the first Iraq’s genotype Lachata. Highest values of fitness and fibre weight plant -1(4.70 microner and 6.64 g) were recorded from Bakhtegan Iran’s genotype. Maximum value for uniformity (85.10 %) was also recorded for Khdorda Iran’s genotype. From the principal component analysis (PCA) shows the angle value between each of the two variables elongation, uniformity and strength is ≤ 90 º it means there is significant correlation between them and via versa